2019
DOI: 10.1016/j.yjmcc.2019.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Protective transcriptional mechanisms in cardiomyocytes and cardiac fibroblasts

Abstract: Heart failure is the leading cause of morbidity and mortality worldwide. Several lines of evidence suggest that physical activity and exercise can precondition the heart to improve the response to acute cardiac injury such as myocardial infarction or ischemia/reperfusion injury, preventing the progression to heart failure. It is becoming more apparent that cardioprotection is a concerted effort between multiple cell types and converging signaling pathways. However, the molecular mechanisms of cardioprotection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 230 publications
(252 reference statements)
0
11
0
Order By: Relevance
“…This result confirmed and suggested that both AET and RET could be included in the rehabilitation training of patients with MI, and patients can choose the suitable exercise mode according to their actual situation. Cardiac injury triggers the activation and differentiation of CFs and disrupts the balance between cardiomyocytes and CFs [40]. Activated CFs increased extracellular matrix (ECM) deposition [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result confirmed and suggested that both AET and RET could be included in the rehabilitation training of patients with MI, and patients can choose the suitable exercise mode according to their actual situation. Cardiac injury triggers the activation and differentiation of CFs and disrupts the balance between cardiomyocytes and CFs [40]. Activated CFs increased extracellular matrix (ECM) deposition [41].…”
Section: Discussionmentioning
confidence: 99%
“…To better study the mechanism of FGF21 on inhibiting cardiac fibrosis, CFs were isolated from the hearts of neonatal mice and treated with H 2 O 2 , rhFGF21 and AICAR. It is well known that oxidative stress is the essential factor of myocardial injury and cardiac fibrosis after MI [40]. In our study, H 2 O 2 treatment up-regulated the levels of TGF-β1, Smad2/3, MMP2, MMP9, and MDA, as well as COL-I and COL-III, and reduced SOD2 protein expression, suggesting the oxidative stress could activate TGF-β1-Smad2/3-MMPs signaling and increase the collagen secretion.…”
Section: Discussionmentioning
confidence: 99%
“…18 Despite providing structural framework for tissues, the alterations in phenotype of fibroblasts may occur during different pathological conditions of different diseases. 2,19,20 Besides, even the same tissue can be populated with several fibroblast subsets with distinct features. 21 During PF, there are several sources of patho-logical fibroblasts, including mesothelial cells, resident fibroblasts, and even bone marrow-derived fibrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism involved in PF remains not fully clear, it has been known that accumulation of activated fibroblasts is one of the key steps in fibrotic progression 18 . Despite providing structural framework for tissues, the alterations in phenotype of fibroblasts may occur during different pathological conditions of different diseases 2,19,20 . Besides, even the same tissue can be populated with several fibroblast subsets with distinct features 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on KEGG pathway enrichment and the result of molecular docking in the core targets, we chose the key proteins of PI3K/AKT/eNOS signaling pathway and the apoptosis-related protein Caspase-3 for validation the mechanisms underlying the anti-MIRI effects of colchicine. The PI3K/Akt signal pathway can regulate the migration, proliferation, differentiation, apoptosis and metabolism of various types of cells, which is connected to cardiomyocyte apoptosis ( Brand et al, 2019 ; Cui et al, 2020 ). PI3K is activated and generates phosphatidylinositol 3,4,5-trisphosphate, which induces the phosphorylation of AKT ( p -AKT), p -AKT then activates endothelial nitric oxide synthase (eNOS) and produces NO, NO produced by eNOS activation has been shown to play an important role in the process of MIRI ( Cohen et al, 2006 ; Ying et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%